Las otras voces. Contextos, narraciones subalternizadas y rutas vitales en ciudadanos diagnosticados con alguna forma de psicosis - Cobo, Carmen Eugenia (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2012)
This work has been conceived as the first formalization made by the author and her research assistants, of a discursive bet around issues derived from her research on the social integration of citizens diagnosed with psychosis. Although it is not about a series of truths that have acquired the forcefulness, nor the necessary maturation time to make of them a finished construct, it is about the concretion of a desire and the expression of a need: to socialize the current state of the reflection on the intersubjective relations in the social integration of citizens diagnosed with psychosis, to submit to analysis, discussion and confrontation the constructed positions; in the search of feedbacks that allow to extend the perspectives from which a route of constant and responsible inquiry on the matter can be constituted, capable of influencing so much in the processes and approaches with citizens diagnosed with psychosis, as in the formation and reflection of those who execute or agenciamos these processes.